The School 10 Program in the context of Alagoas education / O Programa Escola 10 no contexto da educação alagoana - Wellyngton Chaves Monteiro da Silva; Nalú Farenzena (Universidade Estadual de Alagoas, 2020)
This work aims to reconstitute historical and political paths that defined the current conditions of education in the state and that led Alagoas to adopt the school 10 as an educational public policy. The Escola 10 program constitutes a public policy of the state of Alagoas and consists of a pact for Education, initiative of the state Government, uniting state and municipalities, and seeks to guarantee the students ' learning rights, strengthening the regime of Collaboration between the federative entities involved. It has its actions directed to students of elementary School (3rd, 5th and 9th years), with goals related to learning and school flow. The research uses public policy analysis tools and the policy cycle proposed by Stephen Ball and Richard Bowe in order to analytically rebuild the formulation and implementation of school 10. The cut in this article contemplates part of the context of influence that delimited the formulation of the program, and underlined political traits that affect the high degrees of municipalization and relations between state and municipalities in education.